2021
DOI: 10.1017/dmp.2021.370
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptance is associated with Vaccine Hesitancy, Perceived Risk and Previous Vaccination Experiences

Abstract: Objective: This study examines the factors associated with the willingness to get the coronavirus vaccine among individuals aged 18 and above. Methods: This cross-sectional study was conducted in Turkey. The participants aged 18 and older were recruited between December 2020 and January 2021 through conventional social media sites. Snowball sampling was used. An anonymous questionnaire consisted of demographics, vaccination experiences, and perceived risk of coronavirus disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
(68 reference statements)
2
12
1
Order By: Relevance
“…Our analysis identified two age groups (30–49 and 50–69 years old) as more vaccine reluctant than younger people. The stronger propensity of younger people (<30 years old) in our sample to get vaccinated is in contrast with many other published reports of vaccination acceptance increasing with age [ 26 ]. Vaccine hesitancy may stem from young and middle-aged adults considering themselves at lower risk, whereas elderly people are presumably keener to get vaccinated because they feel more exposed to the risk of severe disease and death due to COVID-19 [ 27 ].…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Our analysis identified two age groups (30–49 and 50–69 years old) as more vaccine reluctant than younger people. The stronger propensity of younger people (<30 years old) in our sample to get vaccinated is in contrast with many other published reports of vaccination acceptance increasing with age [ 26 ]. Vaccine hesitancy may stem from young and middle-aged adults considering themselves at lower risk, whereas elderly people are presumably keener to get vaccinated because they feel more exposed to the risk of severe disease and death due to COVID-19 [ 27 ].…”
Section: Discussioncontrasting
confidence: 95%
“…Studies that considered the link between age and intention to get vaccinated against COVID-19 generated different findings [ 12 ]. Age is thought to be one of the demographic factors most likely to influence people’s propensity to get vaccinated [ 26 ]. Our analysis identified two age groups (30–49 and 50–69 years old) as more vaccine reluctant than younger people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study of HCWs in New York did not find differences in hesitancy among different age groups of women, suggesting that higher rates of female vaccine hesitancy may not be simply explained by concerns over fertility, pregnancy, or breastfeeding [90]. Previous negative experiences with vaccines, whether personally or that of a friend or family member [158]. Finally, it is also possible that some HCWs may also hold beliefs that vaccines are generally unsafe, irrespective of events surrounding the COVID-19 vaccine, perhaps contributed to by the fact that some vaccines in the past have been withheld during pregnancy [159] and that initial safety testing for COVID-19 did not include a pregnant cohort and thus initial messaging from the CDC indicated ambivalence towards whether those pregnant should vaccinate [160].…”
Section: Concerns About Safety and Efficacymentioning
confidence: 99%
“…Previous studies in different parts of the world also show a good acceptance rate, ranging from 50% to 85%. [21][22][23][24][25][26] In Peru, the percentage of acceptance has increased in comparison with the study carried out during the first wave, which showed a 49.2% acceptance rate. 27 However, its acceptance is expected to be greater than 90%, as those currently suffering severely from COVID-19 disease are mainly those who have not been vaccinated or who have incomplete doses.…”
Section: Discussionmentioning
confidence: 66%